Crime and Music - Siegel, Dina; Bovenkerk, Frank (Springer International Publishing, 2021)
This unique volume explores the relationship between music and crime in its various forms and expressions, bringing together two areas rarely discussed in the same contexts and combining them through the tools offered by cultural criminology. Contributors discuss a range of topics, from how songs and artists draw on criminality as inspiration to how musical expression fulfills unexpected functions such as building deviant subcultures, encouraging social movements, or carrying messages of protest.Comprised of contributions from an international cohort of scholars, the book is categorized into five parts: The Criminalization of Music; Music and Violence; Organised Crime and Music; Music, Genocide, and Crimes Against Humanity and Music as Resistance. Spanning a range of cultures and time periods, Crime and Music will be of interest to researchers in critical and cultural criminology, the history of music, anthropology, ethnology, and sociology